The moderating role of digital literacy on the relationship between job autonomy, job commitment and innovative work behaviour: an empirical study of selected Malaysian school teachers / Mohammad Fazli Baharuddin - Baharuddin, Mohammad Fazli (2022)
Almost all sectors are highly dependent on employee’s ability to innovate in order to success and sustaining organization’s competitive advantage. Efforts by the government have been implemented in education, where teachers need to have innovative work behaviour which is very helpful in diversifying teaching and learning methods. Nevertheless, even for educational reforms that focused on creativity and innovation for over a decade, the transfer of educational philosophy to practice has not yet occurred. The way of teaching among teachers seems to be still static and monotonous. In addition, teachers still lack of creativity and diversity in teaching and learning methods. Teachers become less innovative in teaching because they are lack of skill in finding various sources of information. Researchers are still examined and observe the factors that influence employee’s innovative work behaviour. By looking for a new research setting, the relationship between job autonomy, job commitment and innovative work behaviour of selected school teachers in Malaysia is the central theme for this study. The discussions related to the theme have been well documented to understand the subject matter. The researcher has also unveiled the moderating role of digital literacy into proposed relationship. With that, three main objectives derived, namely, to examine the perceptions of job autonomy, job commitment, innovative work behaviour, and digital literacy of selected Malaysian school teachers; to examine the influence of job autonomy and job commitment on innovative work behaviour of selected Malaysian school teachers; to assess the moderating effect of digital literacy on the relationship between job autonomy and job commitment on innovative work behaviour. A conceptual research model was first developed based on an extensive literature review, which then the final model was established and used to develop measures and instruments. A quantitative method research design has been employed in this research, which involved three phases of data collection methods, namely pre-testing and validity and reliability of instruments, pilot study and survey. This study was conducted throughout Malaysia with a total of 356 valid questionnaires were obtained from teachers in MRSM under IGCSE program. Structured Equation Modelling (SEM) using Partial Least Square (PLS) was used to analyse the data and to test four hypotheses developed in this study. Based on the analysis of responses, it was discovered that job autonomy and job commitment had a positive influence in affecting innovative work behaviour. The findings also found that significant relationship between job autonomy, job commitment and innovative work behaviour are stronger, when digital literacy is higher. This study added new insights into the body of knowledge by proposing the moderating role of digital literacy on the relationship of job autonomy, job commitment, and innovative work behaviour among school teachers in Malaysia’s boarding schools. With that, the theoretical framework may serve as the guidance for future researchers to conduct a further study on job autonomy, job commitment, digital literacy and innovative work behaviour. Another contribution is the creation of a comprehensive instrument to assess school teachers’ innovative work behaviour.